STUDY OF THE ENVIRONMENTAL NOISE POLLUTION IN PRODUCTION ECONOMICAL ACTIVITIES: STUDY OF THE ENVIRONMENTAL NOISE POLLUTION IN PRODUCTION ECONOMICAL ACTIVITIES - Vladimirov, Lyubomir; Kovachev, Nikolay (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The paper presents results of a study of the environmental noise pollution in sewing and metal working manufacture and the harvester in agriculture. Indiscrete method for noise measurements were created. They are characterized by high precision, wide range of determination of the noise and large sample size of measured values. A probabilistic method for noise pollution assessment is introduced. Seven groups of indicators were used. The method is approbated in practice. The results show large coverage and accuracy.